Marco Polo Iceland with scenic routes and places of interest, fold-out overview map, distance table, index of place names, 1 city map (MairDumont (Firm), 2011)
Cover title.; Includes 4 inset maps.; Accompanied by index in cover with 2 ancillary maps, illustrations and "Mark it!" stickers. Color 1:750,000